1994
DOI: 10.1007/bf02257483
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of the Huntington's disease gene: Evidence against simple inactivation due to an expanded CAG repeat

Abstract: Huntington's disease, a neurodegenerative disorder characterized by loss of striatal neurons, is caused by an expanded, unstable trinucleotide repeat in a novel 4p16.3 gene. To lay the foundation for exploring the pathogenic mechanism in HD, we have determined the structure of the disease gene and examined its expression. The HD locus spans 180 kb and consists of 67 exons ranging in size from 48 bp to 341 bp with an average of 138 bp. Scanning of the HD transcript failed to reveal any additional sequence alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(141 citation statements)
references
References 20 publications
2
135
0
4
Order By: Relevance
“…Our data show that HD-like symptoms can be improved by partial reduction of mutant htt expression, suggesting that complete elimination of mutant allele expression may not be required. Second, disease allele-specific silencing will require identification and testing of disease-linked polymorphisms, one of which has been identified in exon 58 (43). This proof-of-principle work in the HD-N171-82Q-transgenic model provides evidence that disease allele-specific silencing can be accomplished in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Our data show that HD-like symptoms can be improved by partial reduction of mutant htt expression, suggesting that complete elimination of mutant allele expression may not be required. Second, disease allele-specific silencing will require identification and testing of disease-linked polymorphisms, one of which has been identified in exon 58 (43). This proof-of-principle work in the HD-N171-82Q-transgenic model provides evidence that disease allele-specific silencing can be accomplished in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…14 Proteinin ilk 17 amino asidi insan, fare, sıçan ve kirpi balığı htt proteinleri ile %100 homoloji gös-termektedir. 17.…”
Section: Htt Protei̇ni̇unclassified
“…[39][40][41][42][43] The typical sequence beginning at this position is 5¢-GAG.GAG.GAG.GAG-3¢; that for D2642 is 5¢-GAG.GAG.GAG-3¢. The deletion of a codon causes the loss of one of the four tandem glutamate residues in the huntingtin protein.…”
Section: Allele-specific Silencing Of Mutant Huntingtinmentioning
confidence: 99%
“…The three-glutamate species occurs substantially more frequently among HD alleles (38%) than in those without CAG expansion (7%). 39 One skin fibroblast from an HD patient was identified that carried both an HD allele marked by the D2642 deletion and its wild-type counterpart. These cells were transfected with each of four Non-coding small RNAs in developing therapies for HD Y Zhang and RM Friedlander siRNAs designed to target the polymorphic site.…”
Section: Allele-specific Silencing Of Mutant Huntingtinmentioning
confidence: 99%